(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
The present paper is a revised version of a talk given at the Department of Philosophy, Saint Petersburg State University, as part of a series of roundtable discussions held at the Laboratory for Metaphysical Researches in June 2007. At that meeting, the speaker raised the question whether existential thought has a vital contribution to make to our understanding of the postmodern condition. One approach to this question would be to examine the way the central tenets of existential philosophy have been explored. In this respect, the concept of the boundary or limit situation, defined as a universal situation that can neither be surpassed nor subjected to rational analysis, has been a key existential idea. But boundary situations are of two kinds: there are situations that are imposed upon us, and there are those that are brought about by our own actions. Early existentialism tended to focus on limit situations as impositions, but this approach to understanding limit situations leaves us with a conception of the human condition that is static. Moreover, only with the recognition of those limit situations that are created by our own actions (conflict, guilt, history, communication, evil, fidelity, technology, sexuality) do we arrive at a dynamic conception of human freedom. Whilst acknowledging the work of Sartre, Jaspers and Marcel in these areas, it will be the purpose of this paper to illustrate how the fundamental ambiguity that lies at the heart of our self-created boundary situations is revelatory of our capacity for creative freedom-towards-others.